Dialysate as food as an option for automated peritoneal dialysis - Tjiong, Hoey L. (NDT Plus, 2008)
Protein-energy malnutrition is frequently found in dialysis patients. Many factors play a role in its development including deficient nutrient intake as a result of anorexia. Peritoneal dialysis (PD) solutions containing a mixture of amino acids and glucose in an appropriate ratio could serve as a source of food. The authors of this article found that such a dialysis solution when administered to fasting patients who were on nightly automated peritoneal dialysis (APD), as part of a regular dialysis schedule, induced an acute anabolic effect. Also in PD patients in the fed state, dialysis solutions containing both amino acids and glucose were found to improve protein metabolism. It appears that the body responds similar to intraperitoneal and oral amino acid:dialysate as food. Like dietary proteins, intraperitoneal amino acids can bring about generation of hydrogen ions and urea as a result of oxidation. No rise of serum urea levels was found and serum bicarbonate remained within the normal range when a total buffer concentration of 40 mmol/L in the mixture was used. The use of this approach may be an option for PD patients who cannot fulfil dietary recommendations.